Changes in weight, physical activity, sedentary behaviour and dietary intake during the transition to higher education: a prospective study - Deforche, Benedicte (Int J Behav Nutr Phys Act, 2015)
BACKGROUND: The transition to higher education involves a significant life change and might be accompanied with less healthy behaviours. However, the only longitudinal study that spanned the period from high school to college/university was limited to self-reported weight. Other studies assessed objective weight, but only at the start of the first semester at college/university and used retrospective questionnaires to asses health behaviours in high school. This study investigated changes in objectively assessed weight and prospective health behaviours during the transition from high school to college/university in Belgian students and examined which health behaviour changes were related to weight change. METHODS: A sample of 291 students was followed from the final year of high school until the second year of college/university. Body mass index (BMI) and waist circumference were measured objectively. Physical activity, sedentary behaviours and dietary intake were estimated using validated questionnaires. In order to study changes in BMI and health behaviours, 2 × 2 (time × gender) Repeated Measures ANOVA analyses were conducted. A stepwise multiple regression analysis was executed to investigate the association between changes in health behaviours and BMI changes, and the moderating effect of gender. RESULTS: On average students gained 2.7 kg with a greater increase in boys (boys: 4.2 kg, girls: 1.9 kg). Active transportation and sport participation decreased. Some sedentary behaviours (watching TV/DVD, playing computer games) decreased, while others (internet use, studying) increased. Consumption of different foods decreased, while alcohol consumption increased. A higher decrease in sport participation, a higher increase in internet use and a lower increase in studying were related to a greater increase in BMI. An increase in alcohol consumption only contributed to weight gain in boys, whereas a decrease in fruit/vegetable intake only contributed to weight gain in girls. CONCLUSION: We can conclude that the transition to higher education is an at risk period for weight gain and unfavourable changes in health behaviours. Interventions to prevent weight gain in college/university students should therefore already start in high school with a somewhat different focus in boys versus girls.